Synthesis of desformylflustrabromine and its evaluation as an α4β2 and α7 nACh receptor modulator - Kim, Jin-Sung (2007)
Desformylflustrabromine (dFBr; 1) and desformylflustrabromine-B (dFBr-B; 2) have been previously isolated from natural sources, and the former has been demonstrated to be a novel and selective positive allosteric modulator of α4β2 nicotinic acetylcholine (nACh) receptors. The present study describes the synthesis of water-soluble salts of 1 and 2, and confirms and further investigates the actions of 1 and 2 using two-electrode voltage clamp recordings.